Synthesis of (-)-galantinic acid via iterative hydrolytic kinetic resolution and tethered aminohydroxylation - Dubey, Abhishek; Kauloorkar, Shruti Vandana; Kumar, Pradeep (Tetrahedron, 2010)
A new synthetic strategy for (-)-galantinic acid is reported using iterative hydrolytic kinetic resolution and tethered aminohydroxylation as the key steps. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-Aminoalcohol; 3-Diol; Iterative hydrolytic kinetic resolution; selectivity; Tethered aminohydroxylation

Synthesis of indolizidine, pyrrolizidine and quinolizidine ring systems by proline-catalyzed sequential alpha-amination and HWE olefination of an aldehyde - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Kumar, Pradeep (RSC Advances, 2013)
A general procedure for the synthesis of azabicyclic ring systems viz. indolizidine, pyrrolizidine and quinolizidine has been developed utilizing proline-catalyzed sequential alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of an aldehyde as the key step. This method can be further extended to the synthesis of various biologically active natural products containing azabicyclic ring systems.

Stereoselective approach to 2,6-disubstituted piperidin-3-ol: synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline - Jha, Vishwajeet; Kauloorkar, Shruti Vandana; Kumar, Pradeep (European Journal of Organic Chemistry, 2014)
A simple and highly efficient approach to an enantioenriched 2,6-disubstituted piperidin-3-ol skeleton is developed from an aldehyde as a starting material by using organocatalytic and asymmetric dihydroxylation as the key steps. Its application to the total synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline is also reported.
Keywords: alkaloids; Amination; Amino alcohols; synthetic methods; Wittig reactions

Stereoselective approach to indolizidine and pyrrolizidine alkaloids: total synthesis of (-)-lentiginosine, (-)-epi-lentiginosine and (-)-dihydroxypyrrolizidine - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (Organic & Biomolecular Chemistry, 2014)
A simple and highly efficient approach to hydroxylated pyrrolizidine and indolizidine is developed from an aldehyde as a starting material using organocatalytic and asymmetric dihydroxylation reactions as key steps. Its application to the total synthesis of (-)-lentiginosine, (-)-epi-1,2-lentiginosine and (-)-dihydroxypyrrolizidine is also reported.

Stereocontrolled synthesis of Hagen's gland lactones via iterative proline catalyzed alpha-aminoxylation and oxa-Michael addition reactions - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (RSC Advances, 2015)
A simple and efficient synthesis of Hagen's gland lactones was achieved using a sequential alpha-aminoxylation/oxa-Michael approach in a highly diastereoselective manner with assignment of relative configurations. This method was found to be applicable to the synthesis of various other isomers of Hagen's gland lactones.